Peningkatan Kemampuan Personal Branding sebagai Upaya Meningkatkan Daya Saing Pengrajin Gitar Desa Ngrombo, Sukoharjo - Surya, Pinkan; Tama, Ady; Raka Purnama, Bramasetya; Qolbia, Naurah; Salamah, Salamah; Mazala Istiqoma, Binta; Setiawan, Arif (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Ngrombo Village, located in Baki Subdistrict, Sukoharjo Regency, is known as the "guitar village" due to its thriving guitar-making industry. However, guitar craftsmen face several challenges in developing their personal branding. To address these issues, a community service program organized a series of training and mentoring activities focused on product branding, digital marketing, and website management. The training aimed to help craftsmen build a stronger brand identity and expand their market reach. The methods used included Focus Group Discussions (FGD), hands-on training, and ongoing mentoring. The results of this program showed a significant increase in the craftsmen's understanding of personal branding, with some of them beginning to use personal brands and utilize websites for marketing their products. The success of this program has led to recommendations for continued training focused on advanced digital skills, such as social media management, paid advertising, and international marketing strategies. The goal is to enhance the visibility and competitiveness of the guitar products from craftsmen in Ngrombo Village in broader markets. Thus, it is hoped that the guitar craftsmen in Ngrombo Village can continue to grow and compete in this digital era.